2003
DOI: 10.1128/jb.185.5.1608-1615.2003
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Expression of the Haemophilus influenzae Hap Autotransporter Allows Fine-Tuned Regulation of Adhesive Potential via Inhibition of Intermolecular Autoproteolysis

Abstract: The Haemophilus influenzae Hap autotransporter is a nonpilus adhesin that promotes adherence to respiratory epithelial cells and selected extracellular matrix proteins and facilitates bacterial aggregation and microcolony formation. Hap consists of a 45-kDa outer membrane translocator domain called Hap ␤ and a 110-kDa extracellular passenger domain called Hap S . All adhesive activity resides within Hap S , which also contains protease activity and directs its own secretion from the bacterial cell surface via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…Conversely, cleavage may allow Y. pestis to release itself from YapE-mediated interactions with eukaryotic cells. A similar release mechanism has been proposed for the Hap adhesin of Haemophilus influenzae, although Hap relies on autoproteolysis for cleavage (24).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, cleavage may allow Y. pestis to release itself from YapE-mediated interactions with eukaryotic cells. A similar release mechanism has been proposed for the Hap adhesin of Haemophilus influenzae, although Hap relies on autoproteolysis for cleavage (24).…”
Section: Discussionmentioning
confidence: 99%
“…To address this question, we evaluated the extent of autoproteolysis under different conditions of induction, in order to assess if AIDA-I cleavage varied with protein density. Similar experiments were used to characterize the intermolecular cleavage of Hap (14,15). We used plasmid pAg, which contains the aidA and aah genes in their original operon organization but under the control of an IPTG-inducible promoter.…”
Section: Resultsmentioning
confidence: 99%
“…The Haemophilus influenzae autotransporter adhesin Hap is also cleaved after translocation (52). Inhibition of the autoproteolytic cleavage of Hap increased bacterial autoaggregation and adhesion, suggesting that the cleavage acts as a regulation mechanism (15,23,24). These proteins, however, are significantly different from AIDA-I, in sequence and function; thus, the mechanism and function of the cleavage of AIDA-I remain obscure.…”
mentioning
confidence: 91%
“…Hendrixson and St Geme (207) found that the uncleaved cell-associated form of Hap mediates adherence to cultured epithelial cells and promotes bacterial aggregation and microcolony formation, whereas more recent data demonstrated an interaction between Hap and extracellular matrix proteins (135,137,138). Adherence and aggregation are augmented by secretory leukocyte protease inhibitor, a soluble protein component of respiratory secretions that inhibits Hap autoproteolysis.…”
Section: H Influenzae Adhesion and Penetration Protein (Hap)mentioning
confidence: 99%